Implementation of certainty factor method for the diagnosis of tyla fish diseases - Yehezekiel Ramasyah Putra Haloho; Yohani Setiya Rafika Nur; Ummi Athiyah (Institute of Computer Science (IOCS), 2023)
Tilapia is one of the most attractive fish for the people of Indonesia because it can be easily found in traditional markets. Obstacles during the fish farming process are disease transmission in tilapia that is farmed so that it can affect sales and will certainly harm fish farmers. Based on this, an expert system was created in order to diagnose diseases in Tilapia. The purpose of the system is to assist fish farmers in diagnosing and treating diseases of tilapia. The method or technique used in this study is the Certainty factor. The results of the study obtained an output in the form of the disease experienced and also a solution for handling tilapia attacked by the disease using the Certainty factor method. The expert system produced by the research, then tested using blackbox testing where all components in the tested system produce the desired results and match their functionality, and the results of accuracy testing with experts obtain an accuracy value of 96% so that the system is declared accurate